Role of microRNA-499-5p in Early Diagnosis of Acute Coronary Syndrome and its Subtypes Compared with Highly Sensitive Cardiac Troponin –I - Hussein, Ali Abdul Rasool; Issa, Abdulkareem H.; Al Shareeifi, Abbas Naji Muslem (AL-Kindy College Medical Journal, 2024)
Background: Acute coronary syndrome (ACS) is still one of the main causes of morbidity and mortality worldwide, to decrease mortality rates if diagnosed early. The ACS classification into three subtypes depends on electrocardiogram. miRNA-499-5p was found to be substantially elevated in AMI patients as compared with the non-AMI group and healthy control and it was already detectable in the plasma 1h after the onset of chest pain in AMI patientsObjectives: To evaluate the role of measuring serum miRNA-499-5p value in early diagnosis of ACS and compare with hscT-ISubjects and Methods: A total of 120 patients (72 males and 48 females) aged≥30 years were consecutively selected from those who were admitted and diagnosed with ACS. The healthy subjects as controls for this study were recruited from those who had no current illness. The serum miRNA-499-5P and hscT-I were measured.Results: It was shown that miRNA-499-5p levels had an overall significant difference among study groups (p